Cultural heritage and sustainable tourism development - Peralta, Francisco (New York Clanrye International, 2025)
Cultural heritage and sustainable tourism development go hand in hand to preserve and promote the unique identities and traditions of communities while benefiting both locals and visitors. Cultural heritage has physical elements like historic sites, artifacts and traditional crafts, as well as non-physical aspects such as languages, rituals and knowledge systems. Sustainable tourism development ensures that tourism activities respect and enhance cultural heritage. I